The Effect of Maternal Labor Force Participation on Child Development - James‐Burdumy, Susanne (Journal of Labor Economics, 2005)
The effect of maternal employment on child development is examined using fixed effects models. Hausman tests suggest that ordinary least squares models produce biased and inconsistent estimates. Fixed effects results show that only one of three tests (PIAT math) was negatively affected by maternal hours and weeks worked in year 1 of the child’s life. The PIAT reading score was negatively affected by weeks worked in year 1 but not hours worked in year 1. None of the tests were affected by weeks or hours worked in year 2. Finally, weeks worked in year 3 positively affected PIAT math scores.